2002
DOI: 10.1034/j.1600-0625.2002.110502.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic aging vs. photoaging: a comparative histopathological, immunohistochemical, and ultrastructural study of skin

Abstract: Cutaneous aging is a complex biological phenomenon affecting the different constituents of the skin. To compare the effects of intrinsic and extrinsic aging processes, a total of 83 biopsies were collected from sun-exposed and protected skin of healthy volunteers representing decades from the 1st to the 9th (6-84 years of age). Routine histopathology coupled with computer-assisted image analysis was used to assess epidermal changes. Immunoperoxidase techniques with antibodies against type I and type III collag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
334
2
26

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 459 publications
(375 citation statements)
references
References 32 publications
13
334
2
26
Order By: Relevance
“…The symptoms of skin aging process include wrinkling, hyperpigmentation, telangiectasia, enlarged pores and actinic keratoses, and wrinkling and skin elasticity are thought to be the most evident features (El-Domyati et al, 2002;McCullough and Kelly, 2006). Meanwhile, a series of photo-damages caused by chronic UV radiation including texture abnormalities, irregular pigmentation (such as solar keratosis, solar lentigo, and seborrheic keratosis) and even skin tumors, intertwine with the inherent influences and contribute to skin aging in the long run (Rabe et al, 2006;Fisher, 2005;Stern, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms of skin aging process include wrinkling, hyperpigmentation, telangiectasia, enlarged pores and actinic keratoses, and wrinkling and skin elasticity are thought to be the most evident features (El-Domyati et al, 2002;McCullough and Kelly, 2006). Meanwhile, a series of photo-damages caused by chronic UV radiation including texture abnormalities, irregular pigmentation (such as solar keratosis, solar lentigo, and seborrheic keratosis) and even skin tumors, intertwine with the inherent influences and contribute to skin aging in the long run (Rabe et al, 2006;Fisher, 2005;Stern, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The ageing process has a profound effect on the structure and function of this elastic fibre system but, as with the ageing lung, human skin accumulates damage due to both the action of normal metabolic processes and also as a result of interactions with environmental factors. In areas exposed to ultraviolet light, acute or "extrinsic" ageing processes are superimposed on underlying chronic or "intrinsic" ageing mechanisms (El-Domyati et al 2002). These two processes have distinct cosmetic and structural consequences for ageing skin.…”
Section: Cutaneousmentioning
confidence: 99%
“…There is general agreement, however, that the thickness of the stratum corneum does not change with age. In a study comparing the effects of intrinsic and extrinsic ageing, histopathological examination of 83 biopsies from sun-exposed and protrected skin in healthy volunteers aged 6-84 years revealed epidermal thickness to be constant across the decades in both sun-exposed and -protected skin, with the thickness found to be greater in sun-exposed skin [34]. In a different study, the spinous layer of a wrinkle was shown to be thinner at the base than at the flanks [35]; in addition, according to this study, fewer keratohyaline granules are present in the wrinkle base as compared to the flanks.…”
Section: Epidermismentioning
confidence: 99%